1981
DOI: 10.1136/bmj.283.6304.1425
|View full text |Cite
|
Sign up to set email alerts
|

Organochlorine pesticide residues in human fat in the United Kingdom 1976-7.

Abstract: results from earlier studies showed a further decline in residues of pp'-dichlorodiphenyltrichloroethane (pp'-DDT) and dieldrin (HEOD) and increased amounts of hexachlorobenzene residues; concentrations of other compounds were similar to those observed in the studies carried out in 1963-4, 1965-7, and 1969-71. Comparison of the data with those from other countries showed that the concentrations of organochlorine pesticide residues and polychlorobiphenyls in human fat samples from residents of the United Kingd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1983
1983
2012
2012

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Our data provide one of the most up-to-date contamination status reports on PCBs in Japanese human adipose tissue, and these elevated residues suggest continuing exposure to PCBs by Japanese humans. In fact, temporal trend investigations conducted in developed nations such as the United States, Canada, the United Kingdom, the Netherlands, and Japan revealed that there was no significant decline in PCB residues in humans (16)(17)(18)(19)(20). PCB production ceased in Japan in 1972; however, large proportion of PCBs, accounting for approximately > 50% of the cumulative production, still remained in use in older transformers and capacitors (21).…”
Section: Methodsmentioning
confidence: 99%
“…Our data provide one of the most up-to-date contamination status reports on PCBs in Japanese human adipose tissue, and these elevated residues suggest continuing exposure to PCBs by Japanese humans. In fact, temporal trend investigations conducted in developed nations such as the United States, Canada, the United Kingdom, the Netherlands, and Japan revealed that there was no significant decline in PCB residues in humans (16)(17)(18)(19)(20). PCB production ceased in Japan in 1972; however, large proportion of PCBs, accounting for approximately > 50% of the cumulative production, still remained in use in older transformers and capacitors (21).…”
Section: Methodsmentioning
confidence: 99%